IMAGE OF POSTAL AND TELEGRAPH SERVICE COMPANY IN THE COMMUNITY: ANKARA PROVINCE CASE (Third Sector Social Economic Review, 2019)
The aim of this study is to determine the direction of PTT image in the target society(goog or bad), and to evaluate the opinions of the society about the corporate by determining the factors that constitute the perception of the corporate image. According to the research results,it has been seen tahat the corporate image of PTT is perceived as ‘’good’’ by the society. The field survey was conducted in Ankara.Province in november,2018.The survey has been applied by face to face, by telephone and e-mail on 450 participants selected using the easy sampling method.429 questionnaires have been analyzed after the survey.This study examined the identification of the corporate identity of the PTT as well as the differences between the corporate image sub-identitics of the respondents and the demographic characteristic of PTT images.According to the research other important results,the image of PTT in society and whether the image of corporate differs through the demographic characteristics have been examined. In addition,it has also been revealed that the reason why the participants prefer the corporate is tahat the PTT is a reliable institution and that the products and services affered by the participants are low wage.
Keywords: Image; Corporate IImage; PTT; Quality; Visual Idendity; Communication; Corporate Responsability